High-dose dexamethasone induced LPS-stimulated rat alveolar macrophages apoptosis - Zeng S; Qiao H; Lv XW; Fan D; Liu T; Xie D (Dove Medical Press, 2017)
Si Zeng,1,* Hui Qiao,2,* Xue-wen Lv,1 Dan Fan,1 Tong Liu,1 Dongli Xie1 1Department of Anesthesiology, Sichuan Academy of Medical Sciences & Sichuan Provincial People’s Hospital, Chengdu, 2Department of Anesthesiology, The Eye and ENT Hospital of Fudan University, Shanghai, China *These authors contributed equally to this work Abstract: Prolonged administration of an excessive dose of corticosteroids proved to be harmful for patients with acute lung injury (ALI). A previous study has found that repeated administration of an excessive dose of methylprednisolone reduced alveolar macrophages (AMs) in bronchoalveolar lavage fluid (BALF) with an unknown mechanism. This study aimed to investigate the effect of excessive use of dexamethasone (Dex) on BALF AMs in vitro. Transmission electron microscopy and DNA fragmentation analysis demonstrated that 10–4 and 10–5 M Dex induced lipopolysaccharide-stimulated rat AMs apoptosis with downregulation of tumor necrosis factor-α, interleukin (IL)-12 and upregulation of IL-10, transforming growth factor-β. These results indicated that apoptosis might be a novel contribution involved in the detrimental effect of excessive dose of Dex clinically used to treat ALI. Keywords: dexamethasone, alveolar macrophage, lipopolysaccharide, acute lung injury, apoptosis, inflammatory cytokines